التكنولوجيا الاحلالية ودورها في تطوير المنتجات: مدخل الطاقة المتجددة - عبدالجواد، رجب هلال; محمد، أسامة يوسف; متولي، أحمد أحمد صلاح الدين (الجمعية العربية للحضارة والفنون الإسلامية, 2021)
التكنولوجيا الإحلالية وتوظيفها في عملية التصميم الصناعي، مفهوم التكنولوجيا الإحلالية لا يشير ببساطة إلى تكنولوجيا جديدة أكثر جودة بل إلى تكنولوجيا تحل أو تستبدل التكنولوجيا الموجودة بالفعل ولهذا فإنها تزيد من صعوبة الأمور بالنسبة لكثير من المنظمات الصناعية. ومن هنا تناول البحث موضوع التكنولوجيا الإحلالية محاولا توظيفه والعمل على ربطه بعملية تصميم المنتجات الصناعية عن طريق استخدام الطاقات المتجددة كمصدر بديل للتغذية، ودراسة تأثير ذلك على أدائها الوظيفي والهندسي. بالإضافة إلى تناول مصادر الطاقة المتجددة بأنواعها كشكل من أشكال التكنولوجيا الإحلالية ودراسة سبل تسخير تلك الطاقات للانتقال بعملية التصميم الهندسي إلى مستوى آخر لمواكبة التطور السريع لتلك الطاقات ومحاولة الوصول إلى أقصى منفعة هندسية بناء على ما توصلنا له بعد الدراسة الواسعة للعديد من مصادر الطاقة المتجددة. وتتمثل أهمية البحث في تأكيد أهمية دمج مصادر الطاقة الحديثة داخل عملية التصميم وخلال عملية تطوير المنتج ودراسة مدى تأثير ذلك على عدة عوامل كشكل المنتج وتماثله بالإضافة إلى العوامل الجمالية وغيرها. توصل البحث إلى الضرورة الحتمية لعملية إحلال مصادر الطاقة التقليدية بمصادر أخرى مستدامة، تدفع بالمنتجات إلى ضرورة مواكبة تلك العملية لإعطاء أداء وظيفي أفضل وللمحافظة على البيئة، وبالتالي تدفع عملية التصميم إلى مراحل متقدمة وضرورية لتسير جنبا إلى جنب مع التطور السريع لمصادر الطاقة."
Replacement technology and its use in the industrial design process. The concept of substitution technology does not simply refer to a new, better quality technology but rather to technology that dissolves or replaces existing technology, and for this it makes things more difficult for many industrial organizations. From here, the research tackled the topic of substitution technology, trying to employ it and working to link it to the process of designing industrial products through the use of renewable energies as an alternative source of nutrition, and studying the impact of this on their functional and engineering performance. Hiring and working on linking it to the process of designing industrial products through the use of renewable energies as an alternative source of nutrition, and studying the impact of this on their functional and engineering performance. In addition to addressing renewable energy sources of all kinds as a form of substitution technology and studying ways to harness these energies to move the engineering design process to another level to keep pace with the rapid development of these energies and try to reach the maximum engineering benefit based on what we reached after the extensive study of many renewable energy sources. The importance of research is to confirm the importance of incorporating modern energy sources into the design process and during the product development process, and to study the extent of this impact on several factors such as product and similarity in addition to aesthetic factors and others. The research reached the imperative of the process of replacing traditional energy sources with other sustainable sources, pushing the products to the necessity of accompanying that process to give better job performance and to preserve the environment, and thus push the design process to advanced and necessary stages to go hand in hand with the rapid development of energy sources.
Keywords: التكنولوجيا الإحلالية -- التصميم الصناعي -- الطاقات المتجددة -- التنمية المستدامة